Genetic Analysis of Undiagnosed Juvenile GM1-Gangliosidosis by Microarray and Exome Sequencing - Ahmed Bouhouche; Houyam Tibar; Yamna Kriouale; Mohammed Jiddane; Imane Smaili; Naima Bouslam; Ali Benomar; Mohamed Yahyaoui; Elmostafa El Fahime (Case Reports in Genetics)
GM1 gangliosidosis is an autosomal recessive lysosomal storage disorder due to mutations in the lysosomal acid 3-galactosidase gene, GLB1. It is usually classified into three forms, infantile, juvenile, or adult, based on age at onset and severity of central nervous system involvement. Because of their broad clinical spectrum and their similarity to many other aetiologies, including inherited neurodegenerative and metabolic diseases, it is often difficult to diagnose such diseases. Recently, whole exome sequencing (WES) has become increasingly used when a strong hypothesis cannot be formulated based on the clinical phenotype. Here, we present three patients belonging to a consanguineous Moroccan family with a GM1-gangliosidosis with unusual clinical onset and atypical radiological presentation that had eluded diagnosis for over a decade. To identify the disease-causing mutation, we performed a whole exome sequencing and a chromosomal microarray genotyping in order to reduce the number of genetic variants to be interpreted, by focusing the data analysis only on the linked loci. The already known pathogenic missense mutation c.601G>A in GLB1 (p.R201C) was found at homozygous state in the proband V.1 and at heterozygous state in his father IV.1. The mutation was validated by Sanger sequencing and segregated in all the family members according to a recessive mode of inheritance. Outside of the linked loci, we found the EXOSC8 p.Ser272Thr mutation at heterozygous state in all the patients and their mother IV.2. This mutation was reported to cause pontocerebellar hypoplasia type 1C and could act as a modifying factor that exacerbates the brain atrophy of patients. Our study identified the first GLB1 mutation in North Africa in patients with unexpected brain-MRI outcomes extending the clinical spectrum of the GM1-gangliosidosis.